Evidence-Based Implementation Efficiency Analysis of the HIV/AIDS National Response in Colombia - Moreno, Antonio (The World Bank, 2012)
This study on the implementation efficiency of the HIV/AIDS national response in Colombia seeks to examine how it has been implemented-whether it has been done according to the available evidence about the epidemic and as the response was originally planned. The study approaches three specific dimensions of implementation efficiency: (i) programmatic; (ii) budgetary; and (iii) service delivery. The study uses a range of research techniques, including: (i) documentary analysis of key policies, official publications and reports; (ii) semi-structured interviews with representatives of the central government and territorial entities, international and community-based organizations, insurers, care providers, etc.; and (iii) case-study analysis to visualize the ways in which people are cared for in practice. The available data suggest that the HIV/AIDS response is succeeding in keeping the prevalence low and the epidemic concentrated. In recent years, the level of health coverage has increased and the quality of care services has improved. The identified problems in service delivery (mostly related to coverage and access) are linked to system fragmentation and integration, and to the nature of the coordination mechanisms, both at the national and the territorial level. The effectiveness of the response would benefit from re-energized leadership at both the national and local levels-articulated through the existing programmatic framework and coordinating mechanisms. The complexity of the system and the lack of budgetary and expenditure information have impeded the evaluation of the budgetary efficiency of the HIV/AIDS response